Ostα depletion protects liver from oral bile acid load - Soroka, Carol J. (American Physiological Society, 2011)
Bile acid homeostasis is tightly maintained through interactions between the liver, intestine, and kidney. During cholestasis, the liver is incapable of properly clearing bile acids from the circulation, and alternative excretory pathways are utilized. In obstructive cholestasis, urinary elimination is often increased, and this pathway is further enhanced after bile duct ligation in mice that are genetically deficient in the heteromeric, basolateral organic solute transporter alpha-beta (Ostα-Ostβ). In this study, we examined renal and intestinal function in Ostα-deficient and wild-type mice in a model of bile acid overload. After 1% cholic acid feeding, Ostα-deficient mice had significantly lower serum ALT levels compared with wild-type controls, indicating partial protection from liver injury. Urinary clearance of bile acids, but not clearance of [(3)H]inulin, was significantly higher in cholic acid-fed Ostα-deficient mice compared with wild-type mice but was not sufficient to account for the protection. Fecal excretion of bile acids over the 5 days of cholic acid feeding was responsible for almost all of the bile acid loss in Ostα-deficient mice, suggesting that intestinal losses of bile acids accounted for the protection from liver injury. Thus fecal loss of bile acids after bile acid overload reduced the need for the kidney to filter and excrete the excess bile acids. In conclusion, Ostα-deficient mice efficiently eliminate excess bile acids via the feces. Inhibition of intestinal bile acid absorption might be an effective therapeutic target in early stages of cholestasis when bile acids are still excreted into bile.